Recombinant Type XVII Collagen Inhibits EGFR/MAPK/AP-1 and Activates TGF-β/Smad Signaling to Enhance Collagen Secretion and Reduce Photoaging - Ying He; Shiyu Yin; Ru Xu; Yan Zhao; Yuhang Du; Zhiguang Duan; Daidi Fan (Cosmetics)
Studies have consistently shown that long-wave ultraviolet A (UVA) radiation triggers skin photoaging, which is evident as reduced elasticity, a loss of firmness, and signs of aging. There is an urgent need to investigate photoaging mechanisms to devise protective strategies against UVA. The present study aimed to explore the effects of recombinant type XVII collagen on UVA-induced skin aging and uncover its molecular mechanisms, thereby laying a solid theoretical foundation for precise treatments and prevention. We therefore modeled photoaging damage in HaCaT cells and evaluated collagen-related protein and gene expression levels via western blot analysis and real-time quantitative polymerase chain reaction analysis. Immunofluorescent staining was also used to assess collagen secretion and basement membrane protein expression. Recombinant type XVII collagen significantly boosted type IV and type XVII collagen, laminin alpha 5, and integrin β1 production, thus counteracting UVA-induced collagen decline. The polymerase chain reaction analysis revealed matrix metalloproteinase (MMP) downregulation and tissue inhibitor of metalloproteinase (TIMP) upregulation. Modulating the transforming growth factor (TGF)-β/Smad and epidermal growth factor receptor (EGFR)/mitogen-activated protein kinase (MAPK)/activator protein-1 (AP-1) pathways suppressed photoaging. Together, our findings suggest that recombinant type XVII collagen ameliorates UVA-induced damage by reversing MMP and TIMP gene expression, thereby preventing collagen degradation and enhancing basement membrane secretion. These results offer a theoretical basis for potent anti-photoaging products, thus paving the way for innovative solutions against UVA-induced skin aging.